Ummatan Wasaţan dalam Pancasila Perspektif Tafsir M. Quraish Shihab - Khairil Fazal; Juwaini Saleh (TAFSE: Journal of Qur'anic Studies, 2022)
The purpose of this study is to find out how ummatan Wasaţan in Pancasila according to the point of view of understanding M. Quraish Shihab. It was then traced that the idea of wasaţan ummah is an idea that can combine individual and public activities so that there is a balance throughout daily life. This research method uses a literature research approach. The results of the study show that actually according to M. Quraish Shihab the existence of Muslims is still far from the positive side of ummaţan wasaţan, the understanding of ummatan wasaţan in Pancasila is moderate individuals, not left and right, in order to create a just mentality, people who are used as witnesses and all parties witness as an example. There are eight things According to Quraish Shihab about the concept of ummatan wasaţan namely (a) Belief in Allah Almighty and His Messenger; (b) steadiness; (c) Intelligence; (d) Solidarity and solidarity and fraternity; (e) Equity; (f) Commendable; (g) Balance; and (h) Comprehensive. Tujuan penelitian ini ialah untuk mengetahui bagaimana Ummatan Wasaţan dalam Pancasila menurut sudut pandang pemahaman M. Quraish Shihab. Kemudian dilacak bahwa gagasan wasaţan ummah adalah gagasan yang dapat menggabungkan aktivitas individu dan publik sehingga terjadi keseimbangan sepanjang kehidupan sehari-hari. Metode penelitian ini menggunakan pendekatan penelitian kepustakaan. Hasil penelitian menujukkan bahwa sebenarnya menurut M. Quraish Shihab keberadaan umat Islam masih jauh dari sisi positif ummaţan wasaţan, pemahaman ummatan wasaţan dalam Pancasila adalah individu-individu moderat, tidak ke kiri dan ke kanan, agar tercipta mental yang adil, orang-orang yang dijadikan saksi dan semua pihak menyaksikan sebagai contoh. Terdapat  delapan hal Menurut  Quraish Shihab tentang konsep ummatan wasaţan yaitu (a) Keyakinan kepada Allah SWT dan Rasul-Nya; (b) kemantapan; (c) Kecerdasan; (d) Solidaritas dan solidaritas dan persaudaraan; (e) Ekuitas; (f) Terpuji; (g) Keseimbangan; dan (h) Komprehensif.